HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN MOTIVASI DAN KONSENTRASI BELAJAR PESERTA DIDIK - Rehatul Jannah, Laila; Ningtias, Septi Ayu; Mulani, Al Qausar; Netriwati; Fadly Nendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between social media use and students’ learning motivation and concentration. This research employed a quantitative approach using a survey method. The population consisted of all ninth-grade students, with a sample of 60 respondents selected through random sampling. The research instrument was a questionnaire using a Likert scale, which had been tested for validity and reliability. Data were analyzed using Spearman correlation due to non-normal data distribution.The results showed a negative and significant relationship between social media use and learning motivation (r = -0.361; p < 0.05). Meanwhile, there was no significant relationship between social media use and learning concentration (r = -0.090; p > 0.05). Additionally, there was a positive and significant relationship between learning motivation and learning concentration (r = 0.609; p < 0.05). In conclusion, excessive use of social media tends to decrease students’ learning motivation but does not directly affect learning concentration. On the other hand, learning motivation plays an important role in improving students’ learning concentration. Therefore, proper management of social media use and efforts to enhance learning motivation are necessary to support the learning process